Seasonal development of nocturnal blood plasma melatonin concentration in the Hungarian native donkey - Harmat Levente; Chandran Anushya Nathania; Nagy János; Alpár Alán; Somoskői Bence; Fekete Sándor György; Becskei Zsolt; Gáspárdy András (Veterinarski Glasnik)
The domestic donkey (Equus asinus) is a long-day, seasonally oestrous (polyoestrous) species, i.e., its reproduction is regulated by an endogenous circannual rhythm, similar to that of the horse (Equus caballus). In this, periodic melatonin production plays a major role, but little is known about its peripheral concentrations in the donkey. According to the authors’ assumption, the cyclicity characteristic of melatonin concentrations inhorses may also be valid for donkeys. The sampling and statistical processing of the melatonin concentration made it possible to determine the nocturnal rhythm for special periods of the year (solstices, equinoxes) from the basic data. Blood samples were taken from 15 jennies during the year, covering the nocturnal half of the 24 h day. Blood plasma melatonin was assessed using the radioimmunoassay method. Corrected values were calculated for statistical processing. The range of corrected blood plasma melatonin concentrations was established as between 10 and 50 pg mL-1. The midnight melatonin concentration (36.6 pg mL-1) was significantly higher than that determined at 06:00 h and 18:00 h (24.6 and 24.1 pg mL-1, respectively; p<0.001). The blood plasma melatonin concentration of 45.2 pg mL-1 at midnight on the winter solstice was the highest value determined under our geographical conditions. This value differed significantly from the melatonin concentrations at both the summer solstice and the spring equinox (34.2 and 30.7 pg mL-1, respectively). However, the winter solstice value (45.2 pg mL-1) did not differ significantly from the autumn solstice value (36.3 pg mL-1). The results usefully expand the sparse pool of data gathered so far about the development of blood plasma melatonin concentration of domestic ass species.